Using Open Source Software to Engage in Real-Life Problem Solving - Adam, Stewart (LEARNing Landscapes, 2009)
This paper reviews the impact of computers and technology on the learning process of a 17-year-old student. It highlights the key IT experiences that transformed a curious boy into an open source software developer—one with an opinion on teaching practices. In contrast to a culture of ownership and copyright, the paper acknowledges the importance of the concept of using, remixing and sharing information to meet the needs of every learner. This concept is described as creating the pedagogy needed to motivate and engage students in the classroom.